2008
DOI: 10.1186/bf03353127
|View full text |Cite
|
Sign up to set email alerts
|

Tracking F-region plasma depletion bands using GPS-TEC, incoherent scatter radar, and all-sky imaging at Arecibo

Abstract: F-region plasma dynamics has been one of the main foci of the ionospheric research community for decades. The mid-latitude F-region has been considered to be relatively calm; however recent observations using highly sensitive CCD imaging systems and Global Positioning System (GPS) receivers have revealed that mid-latitude F-region mesoscale electrodynamics are more complex and this region is more active than usually assumed. Here we report combined incoherent scatter radar (ISR), imager, and GPS observations o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…COFIs were also observed at Arecibo via an airglow imaging camera. For further discussion relating the Arecibo airglow imager observations to the COFIs observed with the ISR, please see the study by Livneh et al [2007] and Seker et al [2008]. Notice the increase of apparent vertical wavelength with height that is usually taken as being characteristic of thermospheric AGWs.…”
Section: Observationsmentioning
confidence: 99%
See 2 more Smart Citations
“…COFIs were also observed at Arecibo via an airglow imaging camera. For further discussion relating the Arecibo airglow imager observations to the COFIs observed with the ISR, please see the study by Livneh et al [2007] and Seker et al [2008]. Notice the increase of apparent vertical wavelength with height that is usually taken as being characteristic of thermospheric AGWs.…”
Section: Observationsmentioning
confidence: 99%
“…Because of space constraints, only a portion of the results is shown in this paper; please contact the author for the remaining images. For the high‐resolution 22 March 2004 and 5 June 2005 Arecibo results, please see Figures 2 and 3 of Livneh et al [2007] and Seker et al [2008].…”
Section: Observationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Finally, and perhaps most importantly, it has been tentatively found that, at midlatitudes, the MSTIDs usually occur during geomagnetically quiet times [Saito et al, 2002;Shiokawa et al, 2003;Kotake et al, 2006;Tsugawa et al, 2007a;Candido et al, 2008;He and Ping, 2008;Seker et al, 2008] whereas the plumes usually occur at midlatitudes when the geomagnetic activity is high [Garcia et al, 2000;Sahai et al, 2000;Seker et al, 2007].…”
Section: Introductionmentioning
confidence: 99%
“…Otsuka et al (2013) simulated the density structure of MSTID and found the different morphologies for the daytime and nighttime MSTIDs. Although the mechanism of MSTID is still not yet clear, the daytime MSTID might be caused by a gravity wave, while the nighttime MSTID might be generated by the electrodynamical coupling between the Es layer and F region (Shiokawa et al 2003;Saito et al 2007;Otsuka et al 2007;Seker et al 2008;Yokoyama et al 2009). If the MSTID is produced by the electrodynamical coupling effect, a field-aligned structure of density should be observed because the electric field prefers to transport along the magnetic field.…”
Section: Discussionmentioning
confidence: 99%